Developing Instruments for Measuring the Level of Environmental Sustainability Awareness in Chemistry Learning - Pancarani, Mei Linda; Sari, Rr. Lis Permana (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2026)
This study aims to develop a sustainable environmental awareness instrument and test its quality through validity and reliability. This is a development study that develops a sustainable environmental awareness instrument in chemistry learning through revision techniques. The sustainable environmental awareness scale instrument consists of three categories, namely sustainable practice awareness related to activities carried out consistently and sustainably in relation to the environment, behavioral and attitudinal awareness related to understanding the application of environmentally friendly actions, and emotional awareness that shows emotional sensitivity regarding responsibility for environmental issues. Based on the research conducted, a sustainable environmental awareness instrument was developed with 21 statement items that have been declared valid and reliable with a Cronbach's Alpha value of 0.823. Therefore, the developed instrument is suitable for use in further research.